Ground-motion attenuation relationship for the Sumatran megathrust earthquakes. - Megawati, Kusnowidjaja
A representative attenuation relationship is one of the key components required in seismic hazard assessment of a region of interest. Attenuation relationships for peak ground acceleration, peak ground velocity and response spectral accelerations for Sumatran megathrust earthquakes, covering Mw up to 9.0, are derived based on synthetic seismograms obtained from a finite-fault kinematic model. The relationships derived are for very hard rock site condition and for a long-distance range between 200 and 1500 km. They are then validated with recorded data from giant earthquakes on the Sumatran megathrust occurring since year 2000. A close examination of the recorded data also shows that spectral shapes predicted by most of the existing attenuation relationships and that specified in the IBC code are not particularly suitable for sites where potential seismic hazard is dominated by large-magnitude, distant, earthquakes. Ground motions at a remote site are typically signified by the dominance of long-period components with periods longer than 1 s, whereas the predominant periods from most of the existing attenuation relationships and the IBC code are shorter than 0.6 s. The shifting of response spectrum towards longer period range for distant earthquakes should be carefully taken into account in the formulation of future seismic codes for Southeast Asia, where many metropolises are located far from active seismic sources. The attenuation relationship derived in the present study can properly reproduce the spectral shape from distant subduction earthquakes, and could hopefully give insights into the formulation of future seismic codes.
Keywords: Singapore; Sumatra; Mentawai; Subduction; Giant earthquakes; Attenuation; Seismic hazard